DyeIonogels: Proton‐Responsive Ionogels Based on a Dye‐Ionic Liquid Exhibiting Reversible Color Change. (23rd January 2014) - Xie, Zai‐Lai; Huang, Xing; Taubert, Andreas
<x xml:space="preserve">Abstract</x> Transparent, ion‐conducting, and flexible ionogels based on the room temperature ionic liquid (IL) 1‐butyl‐3‐methylimidazolium bis(trifluoromethane sulfonyl)imide [Bmim][N(Tf)2], the dye‐IL (DIL) 1‐butyl‐3‐methylimidazolium methyl orange [Bmim][MO], and poly(methylmethacrylate) (PMMA) are prepared. Upon IL incorporation the thermal stability of the PMMA matrix significantly increases from 220 to 280 °C. The ionogels have a relatively high ionic conductivity of 10−4 S cm−1 at 373 K. Most importantly, the ionogels exhibit a strong and reversible color change when exposed to aqueous or organic solutions containing protons or hydroxide ions. The resulting material is thus a prototype of soft multifunctional matter featuring ionic conductivity, easy processability, response to changes in the environment, and a strong readout signal, the color change, that could be used in optical data storage or environmental sensing.